Ritual in Therapy for Prolonged Grief: A Scoping Review of Ritual Elements in Evidence-Informed Grief Interventions - Wojtkowiak, Joanna; Lind, Jonna; Smid, Geert E. (Frontiers in Psychiatry, 2021)
The aim of this article of to analyze ritual in evidence-informed treatments for prolonged and traumatic grief. A scoping review is conducted in order to give an overview of existing literature on ritual and symbolic interventions in grief therapies for prolonged grief and the type of evidence supporting these interventions. The 22 studies reported in this review reveal a variety of ritual elements ranging from symbolic expression and interaction, writing assignments, dialogue with the deceased or an imaginary person, to farewell ceremonies at the end of the treatment. The interventions are studied within different populations (e.g., bereaved spouses, perinatal loss, grief after violent death, and genocide). Almost all studies show significant effects of the grief treatment, trauma and related symptoms. However, the effects are mostly measured for the entire treatment and not separately for the ritual intervention. In the discussion we focus on the role of ritual and culture in prolonged grief treatment.